Effect of Diagenesis on the Quality of Sandstone Reservoirs Exposed to High-Temperature, Overpressure, and CO2-Charging Conditions: A Case Study of Upper Miocene Huangliu Sandstones of Dongfang District, Yinggehai Basin, South China Sea - Lv, Xiaowei; Fu, Meiyan; Zhang, Shaonan; Meng, Xianghao; Liu, Yi; Ding, Xiaoqi; Zhang, Ya; Sun, Tengjiao (Frontiers in Earth Science, 2022)
The upper Miocene Huangliu sandstones of the Dongfang district are currently regarded as an important exploration target in the Yinggehai Basin. Effected by the anomalous diagenetic environments of high-temperature, overpressure and CO2 fillings, the diagenetic evolution of the Huangliu sandstones appear complicated characteristics and subsequently exert a significant influence on reservoir development. Integrated methods employed in this study include electron microscope, cathode luminescence, X-ray diffraction, scanning electron microscope, electron microprobe, stable isotope analysis, homogenization temperature and physical property tests. By the comparative researches between the AF-1 and AF-2 areas of the Dongfang district, the aim of this study is to investigate the complex diagenetic modifications and their controlling effect on reservoir quality and development mechanism. With similar sedimentary features, the reservoirs in the AF-1 area exhibit slightly higher porosity than the AF-2 area. The permeability in the AF-1 area shows one or two orders of magnitude lower than that of the AF-2 area, and throats size distribution act as a critical factor to cause distinct diversities of permeability. In the AF-1 area, the later appearance of overpressure contributed to stronger compaction intensity and more loss of primary porosity. The dissolution induced by CO2-rich thermal fluids in late stage enhanced the secondary porosity significantly and improved the total porosity. However, extensive dissolution cause abundant precipitations including carbonate cements and authigenic illite in a closed diagenetic system, which lead to the decrease of reservoirs permeability. As for the AF-2 area, earlier occurrence of overpressure restrained mechanical compaction obviously, and further retarded corrosion of orangic acid, which preserved high proportions of primary porosity. Due to lesser impact by CO2 filling, the AF-2 area had a poor intensity of dissolution and cementation, and the authigenic illitization was also restrained significantly, which effectively prevented heavy damage on reservoir quality, and especially for permeability. Based on the diagenetic evolution pathways, two types of porosity evolution patterns are established. The effect degree on diagenesis by high-temperature, overpressure and CO2 filling vary significantly between the AF-1 and AF-2 areas. The two areas show different pathways of diagenetic evolution, forming two development patterns and exhibiting different reservoir types.